Applications of moment problems to the overcompleteness of sequences - Chalendar, Isabelle; Partington, Jonathan R. (Mathematica Scandinavica, 2007)
This paper introduces the notion of a determining function, which is used in order to apply results on the determination of measures by moments to the theory of overcompleteness of sequences in various function spaces, providing strong generalizations of results of Lin and Too. A further application is given to the determination of probability distributions by means of moments of record values.